Pengaruh Kosentrasi dan Frekuensi Pemberian Pupuk Hayati Bio-EXTRIM Terhadap Pertumbuhan dan Hasil Tanaman Wortel (Daucus carota L.) dalam Pot di Dataran Rendah - Riana Amalia; Aluh Nikmatullah; Karwati Zawani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
This study aimed to determine the effect of the concentration and frequency of Bio-EXTRIM biofertilizer applications and their interactions on the growth and yield of carrot (Daucus carota L.) plants cultivated using pots in the lowland. This research was conducted in the rice fields of Siren Hamlet, East Rumbuk Village, East Lombok sub-district, from March toJune 2019, and arranged according to the Randomized Block Design (RBD) factorial with two factors. The first factor was the concentration of  Bio-EXTRIM and the second factor was the frequency of Bio-EXTRIM applications; each consisted of 3 levels and thus resulted in 9 interractio. The interraction were: concentration of 0.25%  with 4 times application, concentration of  0.25% with 5 times application, concentration of 0.25% with 6 times application, concentration of 0.5% with 4 times application, concentration of 0.5% with 5 times application, concentration of 0.5% with 6 times application, concentration of 1% with 4 times application, concentration of 1% with 5  times application, and concentration of 1% with 6 times application. The results showes that the concentration of Bio-EXTRIM biofertilizer had significant effect on the rate of carrot leaf stalks growth, with concentration of 0.25% had the highest leaf stalk growth rate. The frequency of Bio-EXTRIM biofertilizer applications influenced the dry weight of leaf biomass, the middle diameter of the carrot root and the sugar content of the carrot root. The highest dry weight of leaf biomass and diameter of the tuber were obtained in carrot plants treated with Bio-EXTRIM biofertilizer for 4 times, while the sweetest tubers were obtained in carrot plants treated with Bio-EXTRIM biofertilizer for 6 times. However, there was no interaction between the concentration and frequency of Bio-EXTRIM biofertilizers in influencing the growth and yield of carrots grown in the pots in the lowlands